Ysla Campbell (ed.), El escritor y la escena, ts. 1-3. Universidad Autónoma de Ciudad Juárez, 1993, 1994 y 1995. - Aracil Varón, María Beatriz (El Colegio de México, 1995)
Se reseñó el libro: El escritor y la escena, ts. 1-3.